Ultrasound-assisted immersion freezing improves the digestion properties of beef myofibrillar protein - Junguang Li; Chenhao Sun; Xiaonan Yue; Wuchao Ma; Yu Wang; Jiansheng Zhao; Guangsu Zhu; Yanhong Bai (Food Chemistry: X)
This study focused on the effect of ultrasound-assisted immersion freezing (UIF) with different ultrasound power (200, 400, 600 W) on the physicochemical and in vitro digestive properties of beef myofibrillar proteins (BMP). The results showed that the solubility and thermal stability of BMP were significantly increased, when treated with 400 W ultrasound, and the α-helix, β-sheets, β-turns, and random-coil fractions structures content were higher and the fluorescence intensity was closest to that of the control group, demonstrating enhanced structural stability of BMP. The protein digestibility of the UIF-400 W group was significantly enhanced while the particle size of the digested product was reduced, which proved its enhanced in vitro digestion characteristics. Overall, UIF treatment with appropriate power can effectively delay the structural deterioration of proteins, and the loss of thermal stability, enhance the in vitro digestibility of proteins, and promote their digestion and utilization by consumers.